The Lidose Hard Capsule Formulation of Fenofibrate is Suprabioavailable Compared to the Nanoparticle Tablet Formulation Under High-fat Fed Conditions - Roger K Verbeeck; Sophie De Niet; Sonia Lebrun; Mickael Tremege; Tim W. Rennie; Monte Coffiner; Bruno Streel; Bernard Cahay (Frontiers Media S.A., 2015)
Purpose: The therapeutic equivalence of multiple registered fenofibrate formulations, several of which are suprabioavailable and therefore marketed at lower dosage strengths than their reference products, is based on the results of bioequivalence studies. Most of these formulations show a higher bioavailability when taken with a high-fat meal. The relative bioavailability of two of these formulations, the 200 mg Lidose hard capsules and the 145 mg nanoparticle tablets, was assessed when taken with a high-fat meal. Methods: In this single dose, 2-way, randomized, crossover study, 24 healthy subjects received a 200 mg fenofibrate Lidose hard capsule (Test) and a 145 mg nanoparticle tablet (Reference) under high-fat fed conditions. Plasma concentrations of fenofibric acid were measured up to 72 hours by using a validated LC-MS/MS method. Results: The geometric mean ratios (Test/Reference) and the 90% confidence intervals for AUC0-t and Cmax were 1.37 (131.58 - 142.88) and 1.38 (124.60 - 152.93), respectively. The median (range) Tmax values of fenofibric acid were 4.5 h (3.0 - 8.0 h) and 3.25 h (1.0 - 6.5 h) after administration of the Lidose hard capsule and the nanoparticle tablet, respectively. Conclusion: Under high-fat fed conditions the extent of fenofibrate absorption was 37% higher for the 200 mg Lidose hard capsule compared to the 145 mg nanoparticle tablet, which is exactly as expected based on a mg-to-mg weight basis. The results of the present study underline the importance of assessing bioequivalence of fenofibrate formulations under identical fed conditions, and preferentially after a high-fat meal as this condition represents the worst-case scenario. Furthermore, the results of this study demonstrate that the 145 mg nanoparticle tablet is not bioequivalent to the 200 mg Lidose hard capsule when administered under high-fat meal conditions.    This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.